Modeling analysis of depolarization-assisted afterdischarge in hippocampal mossy fibers - Kamiya, Haruyuki (Frontiers in Neural Circuits, 2025)
A strong repetitive stimulus can occasionally enhance axonal excitability, leading to the generation of afterdischarge. This afterdischarge outlasts the stimulus period and originates either from the physiological spike initiation site, typically the axon initial segment, or from ectopic sites for spike generation. One of the possible mechanisms underlying the stimulus-induced ectopic afterdischarge is the local depolarization due to accumulated potassium ions surrounding the axonal membranes of the distal portion. In this study, the mechanisms were explored by computational approaches using a simple model of hippocampal mossy fibers implemented with the structure of en passant axons and experimentally obtained properties of ionic conductances. When slight depolarization of distal axons was given in conjunction with the high-frequency stimulus, robust afterdischarges were triggered after cessation of the repetitive stimulus and lasted for a prolonged period after the stimulus. Each spike during the afterdischarge recorded from distal axons precedes that recorded from the soma, suggesting that the afterdischarge was ectopically generated from distal axons and propagated antidromically toward the soma. Notably, when potassium channels in the model are replaced with non-inactivating ones, repetitive stimuli fail to induce afterdischarge. These results suggested that the inactivating property of axonal potassium channels plays a crucial role in generating the afterdischarge. Accumulated inactivation of potassium channels during strong repetitive stimulation may alter mossy fiber excitability, leading to ectopic afterdischarges from sites distinct from the physiological spike initiation region.